Medieval mystical women in the west
1 online resource (viii, 296 pages).
Keywords: This book explores the rich and varied mystical writings by and about medieval -and a few early modern - women across Western Europe. Women had a profound and lasting impact on the development of medieval and early modern spiritual and mystical literature, both through their own writing and as a result of the hagiographical texts that they inspired. Bringing together contributions by both established and emerging scholars, the volume provides a valuable overview of medieval mystical women with a special focus on the Low Countries and Italy, regions that produced a disproportionately high number of female mystics. The figures discussed range from Hildegard of Bingen, Hadewijch, Mechthild of Magdeburg, Marguerite Porete, Angela of Foligno, Julian of Norwich, and Beatrice of Nazareth to lesser-known women such as Agnes Blannbekin, Christina of Hane, and Maria Maddalena de' Pazzi. The chapters address topics such as the body, pain, desire, ecstasy, stigmata, annihilation, virtue, visions, the tension between exterior and interior experience, and the nature of mystical union itself.